1999
DOI: 10.1111/j.1469-445x.1999.01916.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Streptozotocin Diabetes and Metformin on Erythrocyte Volume and on the Membrane Potential and the Contractile Characteristics of the Extensor Digitorum Longus and Soleus Muscles in Rats

Abstract: The effects of streptozotocin (STZ) diabetes and the antihyperglycaemic agent metformin on the contractile characteristics of the limb skeletal muscles and on erythrocyte volume were examined in rats. After 8 weeks of diabetes, the tetanic tension of the extensor digitorum longus (EDL) muscle decreased and the half-relaxation time of the soleus muscle increased. Endurance decreased in both muscles. Metformin treatment of the diabetic rats did not prevent the development of these contractile changes. Diabetes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
5
21
0
Order By: Relevance
“…1, Table 1). This result was consonant with previous studies showing that the STZ-induced diabetic rat endures a fast-twitch, fiber-specific atrophy of hindlimb muscles (5,14,39). Also, DIA induced a profound decrease of SDH activity compared with CONT (Fig.…”
Section: Effects Of Diabetes On Morphological Properties Of Spinotrapsupporting
confidence: 80%
“…1, Table 1). This result was consonant with previous studies showing that the STZ-induced diabetic rat endures a fast-twitch, fiber-specific atrophy of hindlimb muscles (5,14,39). Also, DIA induced a profound decrease of SDH activity compared with CONT (Fig.…”
Section: Effects Of Diabetes On Morphological Properties Of Spinotrapsupporting
confidence: 80%
“…The age chosen for induction of diabetes is consistent with most previous studies of this model (10,12,23,33,39,40,41,51,55,56). Animals were studied 4 wk after streptozotocin or buffer injection, as this amount of time postinjection is in the middle of the range used in previous studies (10,12,19,23,31,33,39,40,41,51,55,56,63). Furthermore, 4 wk is in line with the two previous diabetic heart gene expression array studies, which examined animals 2 wk post-streptozotocin (31) or 3 days, 4 wk, and 6 wk poststreptozotocin (19).…”
Section: Discussionsupporting
confidence: 57%
“…The age chosen for induction of diabetes is consistent with most previous studies of this model (10,12,23,33,39,40,41,51,55,56). Animals were studied 4 wk after streptozotocin or buffer injection, as this amount of time postinjection is in the middle of the range used in previous studies (10,12,19,23,31,33,39,40,41,51,55,56,63).…”
Section: Discussionmentioning
confidence: 66%
“…Several investigations have been concerned with the effect of diabetes on rodent hindlimb skeletal muscles. They have shown that diabetes impairs muscle contractility and induces muscle atrophy [1][2][3][4] . Different hypotheses have been formulated to explain the alterations in muscle function in the diabetic state (see Discussion).…”
Section: Introductionmentioning
confidence: 99%